L’Orient « systématique et raisonné » : L’exemple du cabinet parisien de don Pedro Davila (1767) - Myriam Marrache-Gouraud (Etudes Epistémè)
In the XVIIIth century, Chinese artefacts became more and more sought after in cabinets of curiosities. But what exactly is the status of these oriental objects ? Are they considered as exotica, or as works of art in their own rights ? To answer this question, this study aims at studying the rhetoric of inventories. It will study in particular the criteria used to include or classify them : are they defined on the basis of what they are made of, how well they are made, their economic value, or because they offer interesting points of comparison with similar objects in Europe ? The inventory made for the sale of of the Davila collection, published in Paris in 1767, will be used to analyze the status of Chinese objects for Enlightenment amateurs and curious. While remaining a source of pleasure and meditation, oriental artefacts are also ordered and classified according to rational categories, through the adaptation of a rhetorics of singularity. A reading of this catalogue will show how the previously dominant discourse of the marvellous gives rise to a more systematic, scholarly discourse.